Reproducibility of transcranial Doppler ultrasound examinations of the ophthalmic artery flow velocity. Issue 1 (January 1993) - Rojanapongpun, P; Morrison, B; Drance, S M
Abstract : Transcranial Doppler ultrasound measurements of ophthalmic artery velocity were made on 88 patients predominantly suffering from glaucoma. Of the four observed parameters, peak velocity, mean-enveloped velocity, diastolic velocity, and resistivity index, the latter was found to be the most reproducible (CV = 5.2%). The variability between patients was approximately twice that of the variability between consecutive measurements. Measurement error appeared to decrease as the operator gained experience.